Intersectional needs and reentry: re-conceptualizing ‘multiple and complex needs’ post-release - Bunn, Rebecca (Criminology & criminal justice, 2019)
For those with multiple and complex needs, re-entering the community after prison is particularly challenging. This article contends that in addition to common intersectional categories such as gender, race, class and age, multiple needs represent another layer of traits that frequently intersect in the lives of ex-prisoners and should be recognized as critical to our understanding of post-release life. Drawing upon the findings of an investigation by the Ombudsman in Victoria, Australia this article explores the merits of intersectionality in understanding the experience of reentry for people with multiple needs. It then identifies the challenges of applying an intersectional approach in practice by considering the example of the Victorian Multiple and Complex Needs Initiative. It is contended that the nature of ‘needs’ within the returning prisoner population is not simply ‘multiple’, but rather ‘intersectional’, and that inadequacies in the wider service system must become our focus if we are to improve the prospects of prisoners post-release.